AB0629 Design of A Randomized, Double-Blind, Placebo-Controlled Phase 2 Clinical Trial of The Toll-like Receptor Antagonist IMO-8400 in Patients with Dermatomyositis. (15th July 2016) - Gordon, P.; Cooper, R.; Chinoy, H.; Isenberg, D.; Lundberg, I.E.; Werth, V.; Gruis, K.; Hurtt, M.; Brevard, J.; Granlund, L.; Fiorentino, D.
Abstract : Background: Dermatomyositis (DM) is a rare idiopathic inflammatory myopathy characterized by an auto-inflammatory immune response in muscle and skin. Multiple lines of evidence suggest Toll-like receptors (TLRs), central components of the innate immune system, play a key role in DM pathogenesis. A retrospective study evaluating muscle biopsy samples showed that TLR9, TLR4 and TLR2 were significantly over-expressed in skeletal muscle and infiltrating cells in DM subjects compared to controls. Over-expression of type I and type II interferons and other cytokines has been demonstrated in DM, suggesting involvement of the NF-κβ pathway. Expression of certain cytokines also had significant positive correlations with expression of TLR9 and TLR4. IMO-8400 is an investigational oligonucleotide-based antagonist of TLRs 7, 8 and 9 that has demonstrated clinical activity in patients with psoriasis. We hypothesize that inhibition of TLR activity in patients with DM with IMO-8400 has the potential to reduce chronic inflammation in affected tissue. Objectives: Our objective was to design a Phase 2 clinical trial of IMO-8400 in DM patients using the Cutaneous Dermatomyositis Disease Area and Severity Index (CDASI) as the primary efficacy endpoint. Specifically, we wished to estimate the placebo response for the CDASI and calculate optimal treatment effect in order to estimate optimal subject numbers and length of trial. Methods: Retrospective analyses were conducted using longitudinal CDASI assessments for 115 unique DM patients seen at the Stanford University outpatient dermatology clinic. Patients with multiple assessments approximately 12 or 24 weeks apart were grouped by the first visit CDASI activity score (<15, 15–19, 20–24 and ≥25), and the change in CDASI activity score between the visits was assessed. Results: Over 24 weeks, a 5 point or greater decrease in CDASI activity score was observed at 31.8% of patient visits, with the change in CDASI activity score ranging from -23 to +27 points across all patients. Because some patients experienced clinically meaningful changes of 4 to 5 points on the CDASI following treatment with standard of care therapies, a 7 point treatment effect was targeted for the IMO-8400 trial. Sample size calculations resulted in 10 patients per treatment group, assuming a standard deviation of 8.5 points over 24 weeks using a Repeated Measures Mixed Model analysis of change from baseline on monthly CDASI assessments (>80% power on a 1-sided test; alpha=0.05). Conclusions: Based on these analyses, we initiated a double-blind, placebo-controlled, 24-week Phase 2 clinical trial in DM patients (NCT number: NCT02612857 ). Key entry criteria include adults with DM aged 18–75 years, CDASI activity score ≥15, clinical symptoms of active muscle disease, and abnormal serum CK or ALD, EMG, muscle biopsy or MRI. Additional outcome measures include MMT-8, timed function tests including 10-meter run walk, and exploratory biomarkers of disease activity. Disclosure of Interest: P. Gordon Grant/research support from: Idera Pharmaceuticals, Inc., R. Cooper Grant/research support from: Idera Pharmaceuticals, Inc., H. Chinoy Grant/research support from: Idera Pharmaceuticals, Inc., D. Isenberg Consultant for: Idera Pharmaceuticals, Inc., I. Lundberg Consultant for: Idera Pharmaceuticals, Inc., V. Werth Consultant for: Idera Pharmaceuticals, Inc., K. Gruis Employee of: Idera Pharmaceuticals, Inc., M. Hurtt Employee of: Idera Pharmaceuticals, Inc., J. Brevard Employee of: Idera Pharmaceuticals, Inc., L. Granlund Employee of: Idera Pharmaceuticals, Inc., D. Fiorentino Grant/research support from: Idera Pharmaceuticals, Inc., Consultant for: Idera Pharmaceuticals, Inc.